Research on the relationship between executive cognition and innovation performance of SRDI SMEs - Chen, Yan; Du, Huilin; Wang, Dehan (Frontiers in Psychology, 2025)
PurposeThis study aimed to explore the relationship between executive cognition and the innovation performance of specialized, refined, distinctive, and innovative small and medium sized enterprises (SRDI SMEs) in China, establish a theoretical framework of the influence mechanism of executive cognition on innovation performance of SRDI SMEs, and give some management implications for SRDI SMEs to improve innovation performance.Design, methodology, and approachThrough theoretical derivation, 409 valid questionnaires from 98 SRDI SMEs in China and statistical analysis techniques, this paper studied the effect of executive cognition of SRDI SMEs on innovation performance and its mechanism.FindingsThis study found that executive cognition has a significant positive impact on innovation performance, compositional capability plays an intermediary role between executive cognition and innovation performance, and organization routine updating enhances the positive relationship between executive cognition and compositional capability.Originality and valueThis study was among the first to investigate the relationship between executive cognition and innovation performance of SRDI SMEs.